2021
DOI: 10.3390/nano12010058
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral and Ultrastructural Changes Induced by Phytosynthesized Silver-Nanoparticle Toxicity in an In Vivo Rat Model

Abstract: (1) Background: The study aimed to assess neurobehavioral, ultrastructural, and biochemical changes induced by silver nanoparticles synthesized with Cornus mas L. extract (AgNPs-CM) in rat brains. (2) Methods: The study included 36 male adult rats divided into three groups. Over a period of 45 days, AgNPs-CM (0.8 and 1.5 mg/kg b.w.) were administered daily by gavage to two of the groups, while the control group received the vehicle used for AgNP. After treatment, OFT and EPM tests were conducted in order to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…The silver content of brain increased 14-fold and 22-fold following the feeding of 30 nm and 10 nm AgNPs, respectively, which was associated with increased gene expression of inflammatory cytokines and impaired cognition [944]. Similar findings were made in rats fed AgNPs [945]. Silver ions may gain access to brain from blood similar to mechanisms that mediate the brain uptake of copper ions.…”
Section: Nanoparticle Neurotoxicologymentioning
confidence: 53%
See 1 more Smart Citation
“…The silver content of brain increased 14-fold and 22-fold following the feeding of 30 nm and 10 nm AgNPs, respectively, which was associated with increased gene expression of inflammatory cytokines and impaired cognition [944]. Similar findings were made in rats fed AgNPs [945]. Silver ions may gain access to brain from blood similar to mechanisms that mediate the brain uptake of copper ions.…”
Section: Nanoparticle Neurotoxicologymentioning
confidence: 53%
“…The greatest toxicity is observed with the chronic administration of either metallic NPs or CNTs/fullerenes. With respect to metallic NPs, toxicity is found after the administration of AuNPs [941][942][943], AgNPs [944,945], iron NPs [946], silica NPs [947], and titanium NPs [948]. Pregnant mice were fed AgNPs orally from the first to last day of gestation [944].…”
Section: Nanoparticle Neurotoxicologymentioning
confidence: 99%
“…The effects of this impairment were shown to be deficits of memory acquisition and maintenance of long-term memory [24]. Other authors also observed steroid-related behavioral disorders, including anxiety-like behavior in mice exposed to citrate-coated AgNPs [45].…”
Section: Discussionmentioning
confidence: 90%
“…Similar results were also shown by Attia et al [44], who also found reduced TAS levels in mice exposed to high doses of citrate-coated AgNPs. In addition, recently, Opris et al [45] also found increased lipid peroxidation products and simultaneous severe ultrastructural changes in neurons and astrocytes in the hippocampus in rats orally exposed to AgNPs phytosynthesized with Cornus mas L. extract. This is in line with the results of our study, which also found elevated TBARS levels, but only in animals that received BSAcoated AgNPs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation